Tingkat Pengetahuan Ibu terhadap Perawatan Perineal dengan Kejadian Diaper Dermatitis pada Bayi - Rinasari Marliaty; Mega Putri (Lembaga Pengembangan Kinerja Dosen, 2024)
Inflammation caused by diapers is one of the most common skin diseases in infants and children worldwide. Diaper rash disrupts the baby's (perineal) skin health and can also interfere with the baby's growth and development. This can occur because the baby becomes fussy, especially during urination or bowel movements, and has difficulty sleeping. To obtain a literature review on maternal knowledge regarding perineal care and the occurrence of diaper dermatitis in infants. Articles published on diaper dermatitis were searched in databases and search engines, including Irandoc, SID, Ovid, PubMed, Google Scholar, ScienceDirect, SINTA, Garuda, and IranMedex, from 2019 to 2023, in both Indonesian full-text articles. Ten journals meet the research criteria based on 30 published and identified journals from 2019-2023. The researchers found that the mother's knowledge level is one-factor affecting perineal care and the occurrence of diaper dermatitis in infants. Based on the reviewed journals, it can be concluded that the level of knowledge is crucial in implementing proper perineal care as it is one of the factors that can influence the occurrence of diaper dermatitis in infants, classified by age, education, occupation, or experience. Therefore, health education is vital in improving maternal knowledge in this regard.